Dinamika Hoax, Post-Truth dan Response Reader Criticism di Dalam Rekonstruksi Kehidupan Beragama - Sonny Eli Zaluchu (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
This research is conducted through literature review to expose and analyze hoax phenomenon, post-truth paradigm, and reader-response criticism. This paper aims to elucidate the social extent to which hoaxes are formed as a result of the presence of post-truth paradigm in the mind of information waves as well as the impact of the digital revolution. The phenomenon will be described through hermeneutical method using reader-response criticism approach in the context of religious life. The research found that spiritual life can be developed in the right way through media-literacy, besides the spread of hoaxes, disinformation, and truth-oriented personal beliefs rather than facts.